Collective trust and stress at work. Evidence from the banking sector - Kaźmierczyk, Jerzy (Publishing House of Wroclaw University of Economics and Business, 2022)
An increasing collective trust reduces stress at work in many countries, regardless of national characteristics. The goal of this paper was to investigate whether collective trust is related to occupational stress among bank employees, where 2,279 bank employees were surveyed. Exploratory factor analysis was used to build a collective trust index based on: openness, care, appreciation, common values, honesty/fairness, loyalty, dyadic trust (a direct question about trust), and job security. Cronbach’s alpha allowed to evaluate the quality of the obtained index. The regression then pointed to those aspects of collective trust and metric variables which were relevant to the level of occupational stress. The most important factors which correlate with stress at work were job security, common values and affective commitment. The authors managed to create a stress management model based on collective trust and components of the metrics.
Argumenta Oeconomica, 2022, Nr 2 (49), s. 151-171
Keywords: collective trust; stress; banking staff; banks; Poland; Russia